SALES GROWTH SEBAGAI PEMODERASI PADA PENGARUH SOLVABILITAS DAN DEFERRED TAX EXPENSE TERHADAP TAX AVOIDANCE PADA PERUSAHAAN PERTAMBANGAN DI INDONESIA - Ervin Ervin Noviani (JURNAL ILMIAH EDUNOMIKA, 2021)
This study aims to analyze sales growth as a moderator of the effect of solvency and deferred tax expense on tax avoidance in mining companies in Indonesia. This research is a quantitative study with tax avoidance as the dependent variable. Tax avoidance is measured by the effective tax rate (ETR). The independent variables studied were soilvability and deferred tax expense and the moderating variable, namely sales growth. The sample of this research is 10 mining sector companies listed on the Indonesia Stock Exchange in 2016-2019. The sample was selected by purposive sampling method with certain criteria. Data analysis was performed by using classical assumption test and for hypothesis testing using multiple linear regression method. The results of this study indicate that sales growth is able to moderate the relationship of solvency to tax avoidance, sales growth is unable to moderate the relationship between deferred tax expense and tax avoidance, solvency has no significant effect on tax avoidance and deferred tax expense has a significant effect on tax avoidance Keywords : tax avoidance, sales growth, solvabilitas, deferred tax expense